2016
DOI: 10.18632/oncotarget.8686
|View full text |Cite
|
Sign up to set email alerts
|

TRIM29 overexpression is associated with poor prognosis and promotes tumor progression by activating Wnt/β-catenin pathway in cervical cancer

Abstract: Dysregulation of TRIM29 has been reported to be involved in tumorigenesis, but the role of TRIM29 in cervical cancer is unclear. In this study, we first examined TRIM29 expression and found that TRIM29 mRNA and protein expression was upregulated in cervical cancer tissues when compared with the matched adjacent cervical tissues. We further detected TRIM29 protein with immunohistochemistry in 150 paraffin-embedded samples from early-stage cervical cancer patients. The results showed that high expression of TRIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 31 publications
(28 reference statements)
1
33
0
Order By: Relevance
“…of Wnt/β-catenin signalling during tumour progression has been highlighted in recent years. Multiple sources of evidence have demonstrated that ATDC promoted the activation of Wnt/β-catenin signalling in various cancers, including non-small-cell lung cancer, cervical cancer, colorectal cancer, pancreatic cancer and glioma 25,29,[47][48][49]. Consistent with these findings, our results demonstrate that ATDC contributes to the activation of Wnt/β-catenin signalling in HCC cells.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…of Wnt/β-catenin signalling during tumour progression has been highlighted in recent years. Multiple sources of evidence have demonstrated that ATDC promoted the activation of Wnt/β-catenin signalling in various cancers, including non-small-cell lung cancer, cervical cancer, colorectal cancer, pancreatic cancer and glioma 25,29,[47][48][49]. Consistent with these findings, our results demonstrate that ATDC contributes to the activation of Wnt/β-catenin signalling in HCC cells.…”
supporting
confidence: 89%
“…13,14,26 ATDC is reported to promote the growth and metastasis of various tumours in vitro or in vivo. 15,16,25,[27][28][29][30][31][32][33] A recent study reports that ATDC is essential for TP63-regulated basal cancer invasive program. 34 Moreover, ATDC exerts its oncogenic effect by promoting the radioresistance and chemo-resistance of tumour cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also indicated that TRIM29 played a crucial role in DNA damage signaling and radioresistance in human pancreatic cancer cells (21). Xu et al demonstrated that TRIM29 was a novel prognostic biomarker for prediction in aggressive cervical cancer patients that need postoperative adjuvant chemoradiotherapy (22). Liu et al suggested that silencing of TRIM29 enhanced chemosensitivity to cisplatin in human lung squamous cancer by increasing cell apoptosis (10).…”
Section: Discussionmentioning
confidence: 99%
“…In mouse and human PanIN lesions, TRIM29 was found to upregulate CD44 via activation of β-catenin signaling, which leads to induction of the EMT phenotype characterized by expression of ZEB1 and Snail (47). In cervical cancer cells, knockdown of TRIM29 was shown to increase E-cadherin expression but decrease N-cadherin and β-catenin expression, which also indicates that TRIM29 promotes EMT (48).…”
Section: Discussionmentioning
confidence: 88%